Altered protein phosphatase 2A methylation and Tau phosphorylation in the young and aged brain of methylenetetrahydrofolate reductase (MTHFR) deficient mice - Sontag, Jean-Marie; Wasek, Brandi; Taleski, Goce; Smith, Josephine; Arning, Erland; Sontag, Estelle; Bottiglieri, Teodoro (Frontiers in Aging Neuroscience, 2014)
Common functional polymorphisms in the methylenetetrahydrofolate reductase (MTHFR) gene, a key enzyme in folate and homocysteine metabolism, influence risk for a variety of complex disorders, including developmental, vascular, and neurological diseases. MTHFR deficiency is associated with elevation of homocysteine levels and alterations in the methylation cycle. Here, using young and aged Mthfr knockout mouse models, we show that mild MTHFR deficiency can lead to brain-region specific impairment of the methylation of Ser/Thr protein phosphatase 2A (PP2A). Relative to wild-type controls, decreased expression levels of PP2A and leucine carboxyl methyltransferase (LCMT1) were primarily observed in the hippocampus and cerebellum, and to a lesser extent in the cortex of young null Mthfr-/- and aged heterozygous Mthfr+/- mice. A marked down regulation of LCMT1 correlated with the loss of PP2A/Balpha holoenzymes. Dietary folate deficiency significantly decreased LCMT1, methylated PP2A and PP2A/Balpha levels in all brain regions examined from aged Mthfr+/+ mice, and further exacerbated the regional effects of MTHFR deficiency in aged Mthfr+/- mice. In turn, the down regulation of PP2A/Balpha was associated with enhanced phosphorylation of Tau, a neuropathological hallmark of Alzheimer’s disease (AD). Our findings identify hypomethylation of PP2A enzymes, which are major CNS phosphatases, as a novel mechanism by which MTHFR deficiency and Mthfr gene-diet interactions could lead to disruption of neuronal homeostasis, and increase the risk for a variety of neuropsychiatric disorders, including age-related diseases like sporadic AD.